The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-08307-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceftolozane/tazobactam versus colistin in the treatment of ventilator-associated pneumonia due to extensively drug-resistant Pseudomonas aeruginosa

Abstract: Resistant strains of Pseudomonas aeruginosa are common pathogens in the intensive care unit (ICU), limiting available therapeutic options. We aimed to compare ceftolozane/tazobactam (C/T) with colistimethate sodium (CMS) in the treatment of ventilator-associated pneumonia (VAP) due to extensively drug-resistant (XDR) Pseudomonas aeruginosa. A retrospective, observational study was performed at a tertiary care ICU. Clinical and microbiological success rate, 28-day all-cause mortality, and adverse events were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In this study, after adjusting for differences between groups, patients treated with ceftolozane-tazobactam had a better clinical cure (adjusted OR (aOR) 2.63, 95% CI 1.31–5.30) and lower acute kidney injury (aOR 0.08, 95% CI 0.03–0.22) [ 39 ]. Concordant results were also reported in two similar case control studies, in which compared to “old antibiotics”, ceftolozane-tazobactam was more effective in the treatment of MDR/XDR P. aeruginosa VAP [ 40 ] and HAP [ 16 ], while reporting a better safety profile in terms of acute kidney injury.…”
Section: Ceftolozane-tazobactamsupporting
confidence: 75%
“…In this study, after adjusting for differences between groups, patients treated with ceftolozane-tazobactam had a better clinical cure (adjusted OR (aOR) 2.63, 95% CI 1.31–5.30) and lower acute kidney injury (aOR 0.08, 95% CI 0.03–0.22) [ 39 ]. Concordant results were also reported in two similar case control studies, in which compared to “old antibiotics”, ceftolozane-tazobactam was more effective in the treatment of MDR/XDR P. aeruginosa VAP [ 40 ] and HAP [ 16 ], while reporting a better safety profile in terms of acute kidney injury.…”
Section: Ceftolozane-tazobactamsupporting
confidence: 75%
“…Although 77% of patients had ventilator-associated pneumonia, only 21% were caused by P. aeruginosa . In this context, in the experimental P. aeruginosa pneumonia model, we found that the administration of IgM-IG combined with colistin was useful in reducing the bacterial lung concentration, which points to the possible efficacy of antibiotics combined with IgM-IG to diminish the mortality of multidrug-resistant P. aeruginosa pneumonia in human beings, which may be as high as 33.3% in patients with ventilator-associated pneumonia treated with colistimethate sodium ( Mogyoródi et al, 2022 ). To extrapolate these results to pneumonia by other multidrug-resistant GNB deserves further research with experimental pneumonia models by other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Some antibiotics efficiency towards P. aeruginosa infections could be improved by context-specific actions. Indeed, in ventilator-associated pneumonia, combination of cephalosporin and beta-lactamase inhibitor ceftolozane/tazobactam (C/T) exhibited both efficacy and safety in treating extensively drug-resistant P. aeruginosa [ 58 ]. However, antibiotic resistance against such a combination has been reported when administered at suboptimal steady-state concentrations of 20 mg/L in the susceptible P. aeruginosa ST175 isolate [ 59 ].…”
Section: Main Textmentioning
confidence: 99%